2011
DOI: 10.3109/09553002.2010.537430
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell niches and other factors that influence the sensitivity of bone marrow to radiation-induced bone cancer and leukaemia in children and adults

Abstract: Purpose: This paper reviews and reassesses the internationally accepted niches or ‘targets’ in bone marrow that are sensitive to the induction of leukaemia and primary bone cancer by radiation.Conclusions: The hypoxic conditions of the 10 μm thick endosteal/osteoblastic niche where preleukemic stem cells and hematopoietic stem cells (HSC) reside provides a radioprotective microenvironment that is 2-to 3-fold less radiosensitive than vascular niches. This supports partitioning the whole marrow target between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…The results revealed equivalent outcomes using the two different stone localization modalities but with the added bene t of no ionization exposure when using the USa technique. A randomized prospective study conducted by Van Besien et al [33] demonstrated similar results, with the USa SWL stone-free rate not being inferior to the FS SWL, but with no need for ionizing radiation. This is probably most bene cial in pediatric patients, as children are 2-7 times more radiation-sensitive than adults [34].…”
Section: Discussionmentioning
confidence: 76%
“…The results revealed equivalent outcomes using the two different stone localization modalities but with the added bene t of no ionization exposure when using the USa technique. A randomized prospective study conducted by Van Besien et al [33] demonstrated similar results, with the USa SWL stone-free rate not being inferior to the FS SWL, but with no need for ionizing radiation. This is probably most bene cial in pediatric patients, as children are 2-7 times more radiation-sensitive than adults [34].…”
Section: Discussionmentioning
confidence: 76%
“…These characteristics are similar to those in in vivo bone marrow, in which active differentiating MSCs occupy perivascular niches and Values are significantly different than control following one-way ANOVA with multiple comparisons (false discovery rate = 0.2). more stem cell-like quiescent MSCs pair up with hematopoietic stem cells in the hypoxic endosteal niche of trabecular bone surfaces (69). Moreover, increased ETC supercomplexes have been observed in MSCs undergoing adipogenic differentiation (70).…”
Section: Discussionmentioning
confidence: 99%
“…Low oxygen tension reduces oxidative stress. In nonocular tissues, an increase in oxygen level can lead to changes in cellular metabolism, proliferation, differentiation and mobilization (Richardson 2011). The greater oxidative damage of the lens in aging adults and reduced intrinsic antioxidant capacity (see section 2.1.2) is paralleled by a decline in oxygen consumption by LECs and lens fiber cells (Hockwin 1971;Kubota et al 2016).…”
Section: Oxygen Tensionmentioning
confidence: 99%
“…In another IR in vivo study, opaque plaquewhich developed at the posterior pole originating from LECs and was induced by high doses of c-rayswas always anuclear in mice, but sometimes nucleated in rats (Hanna and O'Brien 1963). Even though investigations of the role of LEC differentiation in radiogenic cataracts are sparse, published non-ocular studies suggest a major influence of IR on cell differentiation and mobilization (Richardson 2011).…”
Section: Aberrant Lec-to-fiber Differentiation and Emtmentioning
confidence: 99%